Activation of casein kinase II in response to insulin and to epidermal growth factor. - Sommercorn, J (1987)
Insulin treatment enhances casein kinase II (CKII) activity in 3T3-L1 mouse adipocytes and H4-IIE rat hepatoma cells, the magnitude of the activation varying from 30% to 150%. Activation of CKII was apparent after 5 min of exposure of 3T3-L1 cells to insulin, was maximal by 10 min, and persisted through 90 min. The insulin-stimulated activity was inhibited by low concentrations of heparin and was stimulated by spermine. Activation of CKII was effected by physiological concentrations of insulin (EC50 = 0.15 nM), suggesting that the effect is a true insulin response and not one mediated through insulin-like growth factor receptors. Epidermal growth factor (100 ng/ml for 10 min) also activated CKII in A431 human carcinoma cells, which is consistent with other observations that insulin and epidermal growth factor may have some common effects. Insulin stimulation of CKII activity was due to an increase in the maximal velocity of the kinase; the apparent Km for peptide substrate was not altered. Enhanced activity did not appear to result from increased synthesis of CKII protein, because cycloheximide did not block the effect and because an immunoblot developed with antiserum to CKII showed no effect of insulin on the cytosolic concentration of CKII. Because insulin-stimulated CKII activity was maintained after chromatography of cell extracts on Sephadex G-25, it is unlikely that the effect is mediated by a low-molecular-weight activator of the kinase. Rather, the results are consistent with the possibility that insulin activates CKII by promoting a covalent modification of the kinase.